Effects of creatine supplementation during recovery from rapid body mass reduction on metabolism and muscle performance capacity in well-trained wrestlers - Oopik, V.; Paasuke, M.; Timpmann, S.; Medijainen, L.; Ereline, J.; Gapejeva, J. (The Journal of Sports Medicine and Physical Fitness, 2002)
BACKGROUND: The aim of the study was to test the hypothesis that creatine supplementation with concomitant carbohydrate ingestion during recovery period after rapid body mass reduction accelerates the restoration of body mass and physical performance in well-trained wrestlers. METHODS: A double-blind, placebo-controlled cross-over study was conducted on five young healthy male wrestlers, who reduced their body mass by 4.5-5.3% in two series of investigations separated by one month. During 17 hrs recovery period they consumed controlled diet supplemented in random order with glucose (GL trial) or with glucose plus creatine (GL+CR trial). The capacity of the subjects to perform submaximal and maximal (Wmax) intensity work was measured using 5 min intermittent intensity test exercise at the Cybex II device before (Test 1) and after body mass loss (Test 2), also after the recovery (Test 3) on both trials. RESULTS: There was no effect of treatment on the extent of body mass regain during 17 hrs recovery. A significant increase (19.2%) in Wmax from Test 2 to Test 3 was observed in GL+CR trial whereas no change was evident with GL treatment. A strong correlation (r=0.92) was established between the whole body creatine retention and the extent of change in Wmax from Test 2 to Test 3. CONCLUSIONS: The results suggest that creatine supplementation with concomitant glucose ingestion during 17 hrs recovery from rapid body mass loss does not accelerate the restoration of body mass but still stimulates the regain of physical performance in maximal intensity efforts in well-trained wrestlers.